Plants diversity and its potential in Buton Utara Game Reserve, South-East Sulawesi - TAHAN UJI (Biodiversitas Journal of Biological Diversity, 2005)
Study on richness diversity and potential species of plant in two locations in the Buton Utara Game Reserve had been conducted. One hundred and seventy nine species of plant are collected from this area, and 137 species of them are reported as the potential of species. The largest group is timber (76 species) and the other is medicinal plants (41 species). Other data can be gathered as follows 23 species of fruits, 22 species of ornamental plants, 12 species of vegetable, 7 species of fibre plants and 5 species of poisonous plants. The results ofstudy indicated that biti/owala (Vitex coffasus), upi (Intsia palembanica), gufi (Intsia bijuga), nato (Palaquium bataanense), kuru (Elmerillia ovalis), keu uti (Drypetes sibuyanensis), rumbai (Pterospermum celebicum), kondongia (Cinnamomum parthenoxylon), and dongi (Dillenia serrata) were very important as commercial timbers.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: species diversity, potential, Buton Utara game reserve, South-East Sulawesi